Measurement of trilinear gauge couplings in e(+)e(-) collisions at 161 GeV and 172 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1998)
Trilinear gauge boson couplings are measured using data taken by DELPHI at 161 GeV and 172 GeV. Values for WWV couplings (V = Z,γ) are determined from a study of the reactions e+e-→ W+W- and e+e- → Wev, using differential distributions from the WW final state in which one W decays hadronically and the other leptonically, and total cross-section data from other channels. Limits are also derived on neutral ZVγ couplings from an analysis of the reaction e+e-→ y + invisible particles. © 1998 Elsevier Science B.V.